2022
DOI: 10.3390/cells11040693
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Transcriptional Responses of Interactions between Insect Vectors and Plant Viruses

Abstract: This review provides a synopsis of transcriptional responses pertaining to interactions between plant viruses and the insect vectors that transmit them in diverse modes. In the process, it attempts to catalog differential gene expression pertinent to virus–vector interactions in vectors such as virus reception, virus cell entry, virus tissue tropism, virus multiplication, and vector immune responses. Whiteflies, leafhoppers, planthoppers, and thrips are the main insect groups reviewed, along with aphids and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 203 publications
(355 reference statements)
1
16
0
Order By: Relevance
“…Studies have shown that peroxisomes play an essential role in the infective host of psychopathologic fungi, especially the PEX gene involved in the formation and proliferation of peroxisomes, which has been identified in plant pathogens ( Catto et al, 2022 ). In the RNA-Seq data, PEX5 (TRINITY_DN47657_c0_g1) and PEX13 (TRINITY_DN55678_c1_g4 and TRINITY_DN55678_c1_g6) were upregulated, but PEX10 (TRINITY_DN64418_c1_g3) was downregulated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that peroxisomes play an essential role in the infective host of psychopathologic fungi, especially the PEX gene involved in the formation and proliferation of peroxisomes, which has been identified in plant pathogens ( Catto et al, 2022 ). In the RNA-Seq data, PEX5 (TRINITY_DN47657_c0_g1) and PEX13 (TRINITY_DN55678_c1_g4 and TRINITY_DN55678_c1_g6) were upregulated, but PEX10 (TRINITY_DN64418_c1_g3) was downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Aphids, whiteflies, planthoppers, thrips, leaf beetles, and leafhoppers are the major vectors in the transmission of most of the viruses in plants ( Catto et al, 2022 ). M. sacchari transmits the SCYLV in most of the tropical and subtropical regions in a persistent and circulative manner ( Chinnaraja and Viswanathan, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed that the circulative movement of OW (TYLCV) and NW (CuLCrV and SiGMV) begomoviruses within B. tabaci MED differed in their ability to cross the midgut barrier. During circulative movement within B. tabaci , begomoviruses interact with many vector receptors, immune proteins, and/or symbionts’ proteins located at MG, hemolymph, and PSG [ 48 , 98 , 99 , 100 ]. For instance, two B. tabaci MEAM1 midgut proteins, viz., BtCUBN and amnionless (BtAMN), form a BtCubam receptor complex that binds to the capsid protein of TYLCV, resulting in clathrin-mediated endocytosis of TYLCV into whitefly midgut cells [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whiteflies have an innate immune system that has been documented against pathogens [103,104]. The RNA interference (RNAi) pathway is the major mechanism insects use against virus infection [43]. In addition, other innate antimicrobial pathways such as Imd, Toll, JAK-STAT, phagocytosis, apoptosis, and proteolysis were reported to play crucial roles in insects' (Diptera and Lepidoptera) antiviral responses [105][106][107].…”
Section: Discussionmentioning
confidence: 99%
“…Begomovirus infections were reported to influence vector preference and fitness in different ways depending on the host plant [39][40][41][42]. However, the mechanisms involved in such begomoviruses-induced macro-effects on their whitefly vectors are not well understood, and high throughput sequencing platforms have been utilized to understand virus-associated macro-effects on whiteflies [43].…”
Section: Introductionmentioning
confidence: 99%